1998
DOI: 10.1590/s0036-46651998000100011
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HTLV-I Antibodies and Dna in Blood Sample of a Patient With Myelopathy in Nigeria

Abstract: We describe a case of human T-lymphotropic virus type I associated myelopathy in a 50-year old woman in Nigeria. The patient presented with progressive loss of tone to the two lower limbs and later inability to walk. The HTLV-I antibody presence in the plasma collected from the patient was repeatedly detected by enzyme immunoassays (Abbott HTLV-I EIA and Coulter SELECT-HTLV I/II) and confirmed by Western blot technique. In addition, HTLV-I DNA was amplified from the genomic DNA isolated from the peripheral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Furthermore, the findings from this review also show the predominance of infected males as against females widely reported elsewhere. This is consistent with epidemiological studies that show the prevalence of HTLV to vary along sex and reported a higher infection rate in African men or men of African descent [ 39 - 41 ]. This could suggest an etiological factor such as perinatal infectivity as against the transfusion transmission route.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the findings from this review also show the predominance of infected males as against females widely reported elsewhere. This is consistent with epidemiological studies that show the prevalence of HTLV to vary along sex and reported a higher infection rate in African men or men of African descent [ 39 - 41 ]. This could suggest an etiological factor such as perinatal infectivity as against the transfusion transmission route.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with epediomological studies that show the prevalence of HTLV to vary along sex and reported a higher infection rate in African men or men of African descent. 59,61,62) This could suggest an etiological factor such as perinatal infectivity as against the transfusion transmission route. It is imperative to state here that excessive consumption of cassava containing cyanogenic glycosides is a major etiological factor associated with myelopathy, especially tropical ataxic neuropathies in southern states of Nigeria with the highest consumption as compared to the northern regions where zero studies have been reported.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Common causes of diseases of the peripheral nerves such as diabetes mellitus, chronic renal disease, and leprosy are easily excluded by history, clinical examination, and urinalysis. Viral syndromes such as HTLV-1, HTLV-2, and HIV,28 which also come into the differential diagnosis of spinal cord and peripheral nerve diseases, have not been shown to be prevalent in Nigeria 29. Vitamin B 12 deficiency was not demonstrated in patients with TAN in previous studies in Nigeria,30 31 and the prominence of peripheral signs and the absence of motor signs and mental changes distinguishes TAN from vitamin B 12 myelopathy.…”
Section: Discussionmentioning
confidence: 89%